Oral and Dietary Habits, and Immunological and Clinical Impacts on the Inci - U.S. Mahadeva, Rao; Suganya, M; Yadavi, Soondron (2014)
Background: Dental caries is the most common infectious oral disease in human beings and is an oral health problem in many countries. It is a multifactorial disease and bacteria are the cause of caries lesions. However, additional factors have demonstrated an influence on the acceleration or slowing down of the development of new caries lesions. Objective: It is to provide an overview of the caries disease process that will help guide the readers into the world of evidence-based caries management in the beginning of the 21st century and help them understand the need to keep updating in this field. Methods: The reviewers searched 8 databases (MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, LILACS, CNKI, Wanfang, and the South African Department of Health databases) to identify all randomized controlled trials (RCTs), intervention studies, and observational studies published between 1970 and 2014 that met inclusion criteria. Results: Review discussed the results pertained to tooth brushing and dietary habits; relation between - intake of sugars and risk of dental caries; daily total fluoride intake and dental fluorosis as well as caries; unspecific s-IgA with dental caries. Also discussed on caries levels in aggressive periodontitis; prevalence of caries in individuals with Down syndrome; and the correlation study on dental fluorosis with caries risk. Conclusion: In the light of the above results discussed from present review, one can accomplish that implementation of the oral health program for school children should be of higher priority. It has been suggested that one way of improving the cost effectiveness of community-based programs is to target populations at the highest risk of disease.